Different right ventricular maladaptation in heart failure patients with reduced or preserved ejection fraction: diagnostic and prognostic implication. (3rd October 2022) - Palazzuoli, A; Pirrotta, F; Stefanini, A; Barilli, M; Cavati, G; Ruocco, G
Abstract: Background: The prognostic impact of right ventricle (RV) dysfunction and pulmonary hypertension (PH) in patients affected by chronic heart failure (HF) has been well described by several studies in both patients affected by HF with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF). It has been been demonstrated that tricuspidal anular plane systolic excursion (TAPSE)/pulmonary artery systolic pressure (PASP) ratio, may provide additional prognostic information. However, the pathophysiological mechanisms leading to RV dysfunction may differ in HFpEF and HFrEF. Aims: In this study we would like to evaluate: 1. Different RV adaptation in hospitalized HF patients with reduced or preserved EF 2. prognostic significance of an early echocardiographic assessment of RV structure comparing TAPSE/PASP vs s'/PASP in HFrEF and HFpEF. Methods: We included 381 patients included in the study, 209 had HFrEF and 172 had HFpEF who were studied by echocardiography. S' wave and RV longitudinal function strain (RVLS) were obtained by apical four chamber view and optimal visualization of RV lateral free wall. RV diameter was measured at basal level below tricuspidal anular plane. Patients were followed for 6 months after discharge for the composite outcome of cardiovascular death and re-hospitalization. Results: Patients with HFrEF demonstrated a larger RV end diastolic diameter (EDD) compared to HFpEF (43 [37–45] vs 39 [36–44] mm; p=0.009) and more reduced TAPSE (19 [16–21] vs 20 [17–22] mm; p=0.04). Whereas PASP values were similar in both groups. Conversely, s' wave and RVLS were much more reduced in HFpEF (9 [7–11] vs 12 [9–13] cm/sec; p=0.008; 16 [14–21] vs 20 [15–23]% p>0.05) than in HFrEF. TAPSE/PASP was significantly reduced in HFrEF (0.38 [0.29–0.42] vs 0.43 [0.35–0.48]; p=0.02). Conversely s'/PAPS was lower in HFpEF group (0.29 [0.24–0.33] vs 0.25 [0.21–0.31]; p=0.01). At univariate analysis several parameters were related to outcome: TAPSE≤14 mm, (HR 1.70 [1.14–2.52]; p=0.009), PASP≥40 mmHg (HR 1.51 [1.05–2.17]; p=0.02), RVEDD >38 mm (HR; 1.88 [1.36–2.61]; p<0.001), s wave<9 (HR1.88 [1.30–2.41] p<0.001), inferior cave vein diameter>21 mm (HR 1.90 [1.31–2.75]; p=0.001. Multivariable analysis confirmed prognostic role of TAPSE, RVEDD, IVC and s' wave. Therefore TAPSE /PAPS was associated with adverse event in HFrEF but not in HFpEF (HR 1, 75 [1.41–2.92] in HFrEF, p=0.003; HR 1.02 [0.67–1.32] in HFpEF, p=0.55). Whereas, s/PAPS was associated with more increased risk in HFpEF (HR 1.88 [1.65–3.46] in HFpEF, p<0.001; HR 1.34 [1, 08–4.32] in HFrEF, p=0.03). Conclusions: Right ventricular dysfunction and maladaptation are associated with poor outcome in either HFrEF and HFpEF. Tissue excursion and longitudinal strain are much more impaired in HFpEF, whereas RV dilatation and reduced longitudinal function are closely related to HFrEF. Funding Acknowledgement: Type of funding sources: None.